THE INFLUENCE OF BRAILLE SOUND MEDIA ON IMPROVING LITERACY SKILLS OF VISUALLY IMPAIRED CHILDREN AT SLB A KARYA MURNI MEDAN - El Azhar, Yayank; Nur ‘Afifah, Nur ‘Afifah; Harahap, Arni Sofia; Siregar, Sunarsini; Manurung, Ria Anjelina (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2025)
Visually impaired children is a term that refers to people with visual impairments, including children, both totally blind and very limited vision. Based on the results of initial observations and interviews with teachers and principals, it was seen that students were less able/difficult in recognizing Braille writing and one of the factors was because of the limited variation and creativity in using media to improve their writing skills and recognition of Braille writing. This type of research is analytical research. This study used a quasi-experimental plan with a one group pre-test post-test plan, namely measuring variables to groups from the results before and after treatment was given. The data collection technique in this study was through the test method. With the results of the study showing the analysis of the data obtained Zh is 2.05 greater than Zα 5% which is 1.96 so it can be concluded that there is a significant influence of the use of Braille Sound media in improving the literacy skills of blind children at SLB A Karya Murni Medan.